Is there a role for sulfasalazine in the treatment of alopecia areata? - (:unkn) unknown (MOSBY-ELSEVIER, 2007)
Promising results have been published in the past with the use of sulfasalazine in alopecia areata. We also observed maintenance of hair growth in refractory alopecia areata patients who were treated with sulfasalazine in combination with oral corticosteroids for 2 to 6 months and sulfasalazine alone for 4 to 12 months while steroids were being tapered. We believe that, because of the small series reported herein, additional larger prospective studies should be conducted to validate these results.
Keywords: CYCLOSPORINE; THERAPY; EFFICACY; ACID